Effect of different drying methods on the quality attributes of probiotic-enriched cheese chips - Müctebanur Akkaya; Mehmet Çelebi; Ayşe Özçelik; Bedia Şimşek (Mljekarstvo)
In this study, the possibilities of producing probiotic-enriched cheese chips from White cheese (fresh) using various drying methods including natural air drying at 25 °C for 24 hours, microwave drying at 180 W for 120 seconds, and tray drying at 25 °C for 4 hours with an air velocity of 1.3 m/s were investigated. The aim was to examine the effects of different drying systems used in production on the viability of probiotic bacteria (Lactobacillus acidophilus (LA-5) and Bifidobacterium animalis subsp. lactis (BB-12) and the quality characteristics of probiotic-enriched cheese chips. Physicochemical, textural, volatile aroma components, sensory, and microbiological analyses were conducted on the produced cheese chips. The LA-5 value nearest to natural air drying was achieved by a tray dryer (7.32 log CFU/g). One of the highest BB12 counts (6.15 log CFU/g) was found in chips samples that were dried with a tray dryer. The closest results to natural air drying in terms of preserving probiotic bacterial viability, overall acceptability scores, and textural properties were obtained using the tray drying method. In the chips produced by the microwave drying method, the total concentrations of volatile aroma components (alcohols, esters, and hydrocarbons) were found to be higher than in the other samples. The tray drying method can be considered an alternative to the natural air drying method in the production of probiotic-enriched chips.